Pendampingan Masyarakat dalam Pemanfaatan Ampas Sagu menjadi Pupuk Organik Bokashi di Kampung Mosso Kota Jayapura - Lada, Yulius Gae; Mangaluk, Efraim; Stefanie, Selmi Yohana; Sama, Anius (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
In the sago processing process through extraction of sago pith, sago dregs will be produced which is waste in sago processing. Sago dregs contain 65.7% starch and the rest is crude fiber, crude protein, fat and ash. Apart from that, sago dregs contain 21% lignin and 20% cellulose which can be used as raw material to be used as bokashi fertilizer. This service was carried out in Mosso village, Jayapura City and aims to empower the community to process sago dregs into useful organic fertilizer. The methods used in this service are counseling, field practice and discussion. The public is invited to use sago pulp which is usually thrown away and process it into bokashi fertilizer. The community service activities carried out produce something of value and benefit to the local community. The community seems to be actively involved in making bokashi fertilizer by utilizing organic waste which can be directly applied to their agricultural land. Apart from that, it creates community awareness in handling sago waste in their environment.